2003
DOI: 10.1074/jbc.m212773200
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Octylation Rescues an Inactive T20 Mutant

Abstract: T20, a synthetic peptide corresponding to a C-terminal segment of the envelope glycoprotein (gp41) of human and simian immunodeficiency viruses, is a potent inhibitor of viral infection. We report here that C-terminal octylation of simian immunodeficiency virus gp41-derived T20 induces a significant increase in its inhibitory potency. Furthermore, when C-terminally octylated, an otherwise inactive mutant in which the C-terminal residues GNWF were replaced by ANAA has potency similar to that of the wild type T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…The gp120 an inhibitory potency similar to that of the wild-type T-20 (62). In the present study, we found that C-terminal octylation can also rescue a low inhibitory activity of HIV-1 IIIB gp41-derived T-20-ANAA mutant ( Fig.…”
Section: T-20 May Interact With N46 Which Overlaps N36 and N36-f10; supporting
confidence: 56%
See 1 more Smart Citation
“…The gp120 an inhibitory potency similar to that of the wild-type T-20 (62). In the present study, we found that C-terminal octylation can also rescue a low inhibitory activity of HIV-1 IIIB gp41-derived T-20-ANAA mutant ( Fig.…”
Section: T-20 May Interact With N46 Which Overlaps N36 and N36-f10; supporting
confidence: 56%
“…It has been reported that the T-20 analog with mutations in the tryptophan-rich domain, T-20-ANAA, has no HIV-1 fusion inhibitory activity, but the membrane-anchoring T-20-ANAA has similar anti-HIV-1 activity as the wild-type T-20 (61). C-terminal octylation rescue the inactive ANAA mutant of T-20-like peptide derived from the SIV gp41 (62). These suggest that interaction of T-20 and the target membrane is necessary for T-20-mediated membrane fusion inhibitory activity.…”
Section: T-20 Targets Multiple Sites In Gp120/gp41mentioning
confidence: 77%
“…They have also reported that the ability of T20 to inhibit membrane fusion at a post-lipid mixing stage is correlated with its activity to bind and oligomerize on the membrane surfaces (35). It was proven that the C-terminal WNWF motif of T20 is important for its anti-HIV-1 activity, because deletion of this motif or substitution of WNWF with ANAA results in loss of anti-HIV-1 activity, and octylation of ANAA mutant rescues T20-mediated fusion inhibitory activity (22,24,36). von Laer and co-workers (37) have demonstrated that the wild-type T20 and the ANAA mutant T20 have similar anti-HIV-1 activities when both peptides are anchored to the target cell membrane by fusion to a transmembrane domain.…”
Section: Discussionmentioning
confidence: 99%
“…Veiga et al (38) have shown that T-1249, an analogous peptide of T20, and its C-terminal peptide inhibit HIV-1 fusion by interacting with lipid bilayers. The tryptophan-rich (or lipid-binding) domain in the membrane proximal region of gp41 was shown to play important roles in HIV-1 fusion (22,36,39), because it may bind to the membrane surface (40) and participate in oligomerization of gp41 to form fusion pores in the membrane (23,35,41,42). Shnaper et al (43) have shown that the ordered and cholesterol-rich membranes can be destabilized by the gp41 CHR region.…”
Section: Discussionmentioning
confidence: 99%
“…We initially focused on the last four residues of T20: the WNWF sequence known to play a critical role in HIV-1 inhibition. Substituting Ala residues for the three aromatic amino acids (WNWF 3 ANAA) functionally ablates the potent antiviral activity of the peptide (1,24,25). However, recent studies suggest that the WNWF sequence may not directly bind the gp41 N-HR (38).…”
mentioning
confidence: 99%